(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The study investigates into the critical facets of mission management within the Ikwerre South District of the Assemblies of God Church, underscoring its pivotal role in church growth and community influence. It meticulously examines the conceptual framework of mission management, tracing its origins and evolution in the district, and delineating the key strategies employed to enhance ecclesiastical outreach and consolidation. Furthermore, the investigation identifies and scrutinizes the myriad challenges impeding effective mission management, ranging from resource limitations to communication barriers, and evaluates the consequential impact of these strategies on church expansion and community engagement. At the core of the study is the acknowledgment of mission management as an indispensable driver of church growth, facilitated by coherent strategies and policies that align with the church’s foundational objectives of evangelism and discipleship. The narrative highlights the instrumental roles of church leaders like Rev. Charles Allison and Rev. Ahamba Simon in propagating the faith through concerted evangelistic and mission activities, thereby catalyzing the establishment of new congregations and fortifying the spiritual fabric of the community. Despite the notable successes, the research delineates persistent challenges that curtail the efficacy of mission endeavors, emphasizing the need for strategic interventions to surmount these obstacles. Conclusively, the study advocates a series of recommendations aimed at bolstering mission management practices within the district. These include enhancing the mission acumen of church leaders and members, conducting thorough assessments of mission impacts, addressing logistical and operational hindrances, and leveraging modern technological tools to invigorate mission activities. By embracing these suggestions, the Assemblies of God Church in Ikwerre South District can amplify its missionary impact, ensuring sustained growth and a profound community presence.